Easy Fabrication of Highly Thermal-Stable Cellulose Nanocrystals Using Cr(NO3)3 Catalytic Hydrolysis System: A Feasibility Study from Macro- to Nano-Dimensions - Chen, Y.W.; Tan, T.H.; Lee, H.V.; Hamid, Sharifah Bee Abd (MDPI, 2017)
This study reported on the feasibility and practicability of Cr(NO3)3 hydrolysis to isolate cellulose nanocrystals (CNCCr(NO3)3) from native cellulosic feedstock. The physicochemical properties of CNCCr(NO3)3 were compared with nanocellulose isolated using sulfuric acid hydrolysis (CNCH2SO4). In optimum hydrolysis conditions, 80 °C, 1.5 h, 0.8 M Cr(NO3)3 metal salt and solid-liquid ratio of 1:30, the CNCCr(NO3)3 exhibited a network-like long fibrous structure with the aspect ratio of 15.7, while the CNCH2SO4 showed rice-shape structure with an aspect ratio of 3.5. Additionally, Cr(NO3)3-treated CNC rendered a higher crystallinity (86.5% ± 0.3%) with high yield (83.6% ± 0.6%) as compared to the H2SO4-treated CNC (81.4% ± 0.1% and 54.7% ± 0.3%, respectively). Furthermore, better thermal stability of CNCCr(NO3)3 (344 °C) compared to CNCH2SO4 (273 °C) rendered a high potential for nanocomposite application. This comparable effectiveness of Cr(NO3)3 metal salt provides milder hydrolysis conditions for highly selective depolymerization of cellulosic fiber into value-added cellulose nanomaterial, or useful chemicals and fuels in the future.